Pesantren in Contemporary Indonesia: Negotiating Between Equity and the Market - Isbah, M. Falikul; Sakhiyya, Zulfa (2023)
Pesantren, Islamic boarding school in Indonesia, has spanned historically from pre-colonial era to contemporary times. Adaptations, innovations, and adjustments have been made to maintain the relevance, aspired vision, and marketability of this educational model. Studies have pointed out its important contribution in introducing Islamic scholarship and learning tradition, moderating traditionalism and aspired modernization, as well as its contribution to socio-economic development. Despite the changing landscape of Indonesian socio-economic development and increasing number of Muslim middle class, this chapter explores the struggle experienced by pesantren to reconcile the tension between equity principles and market orientation. It fills the gap in the literature by arguing that pesantren has maintained its consistency in providing alternative education and catering to those of lower-class origin. We draw on empirical research with pesantren leaders, teachers, parents, and students in several pesantren in Yogyakarta, Central Java, East Java, South Sulawesi, Aceh, and West Nusa Tenggara.